Effect of pore water chemistry on hydro-mechanical behavior of compacted expansive clay - Vanda, Yaser; Avestakh, Saber (Asesoria & Tutorias Investigacion Cientifica Educacion, 2019)
Pore fluid science may seriously change the concoction organizations of dirts by methods for interchangeable cations. The point is to decide the rate of progress in a portion of the geotechnical engineering properties of clayey soils when presented to salts regarding refined water. Thus, we gathered high expansive clays from sport stadium in eastern Mediterranean university, north Cyprus. The results illustrate that the solution concentration straightly affects a range of parameters ranging from the evaporation tensile strength, unconfined compression to the internal stress that develops at specific gravimetric water contents.
Keywords: unsaturated soils; desiccation; shrinkage; chemistry